Pengaruh Kadar TiO2 Terhadap Kekuatan Bending Komposit Serbuk Al/TiO2 - Lilik Dwi Setyana; Toto Rusianto (Institute of Research and Community Outreach, Petra Christian University, 2005)
Aluminum fine powder as the matrix and TiO2 as the reinforcement is known as Al/metal matrix composite, that can be produced by powder metallurgy. The research of Al/TiO2 MMC with various content of reinforcement was 0, 2, 4, 6 and 8% weight of TiO2. Green body was produced with variuos compacting pressures 400 and 500 MPa, then sintered at 550 oC for 5 hour. Optical and SEM were used to observe the microstructures. Mechanical properties of the specimens including Brinell hardness and modulus of rupture by four point bending. The results of the research show that Brinell hardness number, modulus of rupture and density of composites increases with increasing compacting pressure. The optimum properties were achieved on the composites containing 4% weight of TiO2 were modulus of rupture was 82 kg/mm2, hardness was 42 BHN and density 2.57 gr/cm3 with compacting pressure of 500 MPa. Abstract in Bahasa Indonesia : Aluminium serbuk sebagai matrik dan TiO2 sebagai penguat dikenal sebagai bahan komposit matrik logam (MMC), yang dapat diproduksi dengan teknik metalurgi serbuk. Dalam penelitian ini komposit Al/TiO2 dengan variasi penambahan unsur penguat sebesar 0, 2, 4, 6 dan 8% berat TiO2. Pembentukan green body dengan tekanan kompaksi 400 dan 500 MPa, dan proses sinter pada suhu 550 OC selama 2 jam. Pengujian meliputi uji bending dan kekerasan brinell, pengamatan srtuktur mikro menggunakan SEM dan mikroskop optik. Hasil penelitian menunjukan kekerasan dan kekuatan bending meningkat dengan meningkatnya tekanan kompaksi. Komposisi optimum dicapai pada komposisi Al/TiO2 4% berat, dengan kekuatan bending sebesar 82 kg/mm2 dan kekerasan 42 BHN pada pembentukan dengan tekanan kompaksi 500 MPa. Kata kunci: metalurgi serbuk, Al/TiO2, Komposit.